2011
DOI: 10.4028/www.scientific.net/kem.487.253
|View full text |Cite
|
Sign up to set email alerts
|

Research on Subsurface Damage After Abrasives and Fixed-Abrasive Lapping of K9 Glass

Abstract: Fixed-abrasive lapping (FAL) is a new machining technology and is adopted to manufacture hard brittle materials to obtain the high surface quality. In the same machining condition, K9 glasses are lapped by abrasives and fixed-abrasive, respectively. Two grain sizes of diamond abrasives are adopted in every lapping means. Differential chemical etch method (DCEM) is employed to measure the depth of subsurface damage (SSD) of different lapping means. Surface damages are compared by Microscope. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results show that the material removal rate of fixed abrasive lapping is about 20 times of that of conventional loose abrasive lapping process, and the roughness is close to the conventional one [5]. Fixed abrasive lapping technology is a promising progress to instead of conventional loose lapping progress [6,7].…”
Section: Introductionmentioning
confidence: 87%
“…The results show that the material removal rate of fixed abrasive lapping is about 20 times of that of conventional loose abrasive lapping process, and the roughness is close to the conventional one [5]. Fixed abrasive lapping technology is a promising progress to instead of conventional loose lapping progress [6,7].…”
Section: Introductionmentioning
confidence: 87%
“…Nanomap500LS Surface Profilometer was used to test surface roughness. Differential chemical etch method (DCEM) was selected to measure the depth of SSD after lapping [13,16].…”
Section: Methodsmentioning
confidence: 99%
“…Li et al designed different hardness and abrasive concentration of fixed abrasive polishing pad combination, analyzing the influence of pad features on MRR, Surface topography and surface roughness [12]. Li et al found that fixed abrasive lapping could get small surface damage and shallower depth of SSD than that of free abrasive lapping [13]. Tian et al have analyzed surface roughness, surface topography and material removal rate of glass polishing by using fixed abrasive polishing instead of the conventional chemical mechanical polishing [14].…”
Section: Introductionmentioning
confidence: 99%
“…Then, surface material removal is uniform, machining process is simple, and the pollution of polishing slurries to environment is little [6]. In nano machining process, the slurry chemical action produces a softened layer on workpiece surface and affects self-conditioning performance of pad [7]. With the passivated abrasives falling off, new sharp-edged abrasives reveal continually.…”
Section: Introductionmentioning
confidence: 98%